Sporadic melanotic schwannoma with overlapping features of melanocytoma bearing a GNA11 mutation in an adolescent girl. Issue 6 (24th December 2016) - Tatsi, Christina; Bacopoulou, Flora; Lyssikatos, Charalampos; Belyavskaya, Elena; Faucz, Fabio R.; Stratakis, Constantine A.
Abstract: Melanotic schwannoma (MS) is a soft tissue neoplasm that shares histologic features with melanocytic tumors and schwannomas. A type of MS, called psammomatous MS (PMS), is associated with Carney complex (CNC), which is caused by PRKAR1A mutations. Other pigmented neoplasms, such as uveal melanomas and melanocytomas (MCs), are associated with genetic defects in other genes including GNA11 . We report an adolescent female with a large sporadic mesenteric MS with complex histologic findings reminiscent of both PMS and MC. The lesion carried a mutation of the GNA11 gene. We conclude that sporadic MSs may occur rarely in adolescents without CNC; MSs may also be associated with somatic GNA11 mutations.